One virus, two countries : what Covid-19 tells us about South Africa - Friedman, Steven (Wits University Press, 2021)
In spite of having arguably the best developed health system in Africa, government and scientific responses to the COVID-19 pandemic have fallen short. Steven Friedman explores evidence that South Africa's adoption of a 'First World' approach has made the country unable to respond in a way which would have protected most citizens.